KADAR TOTAL VFA DAN N-NH3 PADA PAKAN RUMINANSIA DENGAN PENGGUNAAN LEGUMINOSA POHON YANG BERBEDA BEBAGAI SUMBER PROTEIN SECARA INVITRO - Merryafinola Ifani; Andran Amar Gunawan; Agung Prasetyo Nugroho (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The study entitled Total Concentrations of VFA and N-NH3 in Ruminant Feed Using Different Tree Legumes with Various Protein Sources In Vitro, aims to determine the optimal mulberry leaf tannins to be given to livestock in vitro and to determine the effect on total VFA and N-NH3 in vitro. Materials and methods. The material used in the in vitro experiment was rumen fluid from three beef cattle at the Bantarwuni Slaughterhouse, Kembaran District, Banyumas Regency. The feed ingredients used were 40% field grass, 30% cassava, 20% pollar, and 10% from several protein sources (soybean meal (R1), calliandra leaves (R2), lamtoro leaves (R3), and indigofera leaves (R4). The study was conducted in vitro using an experimental method with 5 different treatments, each treatment was repeated 4 times so that there were 20 treatment units.The measured variables were total VFA production and ammonia nitrogen (N-NH3). Results. The results showed that the use of Indigofera leaves in the ration produced the highest total VFA and N-NH3, namely 111.00 ± 20.68 mM and 9.90 ± 0.66 mm. Conclusion. It was concluded that the use of protein source feed in the form of tree legumes can be used as a substitute for soybean meal as feed for ruminants, Indigofera Zollingeriana is a tree legiminosa which is the best substitute for soybean meal.